Omalizumab in patients with severe asthma and persistent sputum eosinophilia - Mukherjee, Manali (Allergy Asthma Clin Immunol, 2019)
Omalizumab, a recombinant humanized monoclonal antibody targeting the IgE molecule, is the first biologic approved for moderate-to-severe allergic asthmatics, who remain uncontrolled despite high dose inhaled corticosteroid and bronchodilators. Steroid-sparing effect of omalizumab has not been demonstrated in asthmatics with persistent airway eosinophilia in a randomised controlled trial till date. From this double-blind, placebo-controlled, multi-centred, randomized parallel group design, we report that omalizumab is possibly inadequate to control sputum eosinophilia, and therefore may not have a steroid-sparing effect, especially in those maintained on oral corticosteroids daily. This needs to be confirmed or refuted in a larger trial, which may be a challenge with respect to recruitment, since there are currently three additional biologics available to prescribe. Trial registration Clinicaltrials.gov, NCT02049294, Registered 30th January 2014, https://clinicaltrials.gov/ct2/show/NCT02049294 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13223-019-0337-2) contains supplementary material, which is available to authorized users.